Komparasi Nilai Daya Dukung Tanah Lempung Ditinjau dari Hasil Uji Skala Penetrasi Konus Dinamis, Uji CBR Laboratorium dan Uji Kuat Tekan Bebas - Nursar, Achmad Satria; Iswan, Iswan; Setyanto, Setyanto (Universitas Lampung, 2015)
Soil bearing capacity can be determined with several kind of test, that could produce different testresult for same sample in accordance to characteristics of test equipment and main targets of eachtest equipment in determining soil parameters. This research aimed to compare characteristics ofsoil bearing capacity that obtained from DCP (Dynamic Cone Penetrometer) test, LaboratoryCBR test, and UCS (Unconfined Compressive Strength) test.The soil sample which tested on this research was from Margakaya village and Palputih village,District of Jati Agung, South Lampung and Blimbing Sari village, District of Jabung, EastLampung. Soil sample for Laboratory CBR test was made by compaction. Meanwhile, soilsamples for UCS test was undisturbed soil and remoulded sample.The result of research showed that the CBR value of DCP test result was greater than theLaboratory CBR test result with margin less than 1%. The CBR value was directly proportional tothe compressive strength of its soil. Meanwhile, the DCPI value of DCP test result was inverselyproportional to the design CBR value and the compressive strength of its soil.Keywords: California Bearing Ratio, DCPI, clay, compressive strength